Identifying Sixth Grade Students’ Misconceptions on Solar System - Putri, Febiola Eka; Hermita, Neni; Zufriady, Zufriady; Wijaya, Tommy Tanu (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
The purpose of this study was to determine sixth grade students’ misconception on the solar system. This study uses a sampling technique with a total sample of 88 students. This research uses the descriptive quantitative method. This research aims to describe the misconceptions on the material of the solar system in class 6 of public elementary school in Pekanbaru, data collection techniques using the Four Tier Test. The results showed that students' misconceptions were categorized as "medium" with an average of 47.58% of 88 students. The highest misconception on material related to the characteristics of stars with a misconception level of 67.61% with this level can be said that there are still many students who are investigated experiencing misconceptions. The lowest misconception is 27.27%, which is material about the sun as the center of the solar system.